Efektivitas Antioksidan Tanaman Faloak (Sterculia quadrifida) - Anna Maria Dewajanthi; Felicia Carlista Ventura Santosa; Flora Rumiati; Handy Winata (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Faloak plant is widely used by people in East Nusa Tenggara Province to treat various diseases. The bark of the faloak tree is believed to increase stamina, treat liver dysfunction, ulcers, and typhoid. Often also used to clean the vagina and treat menstrual disorders. Traditional medicine of the faloak plant has been widely used, but there has not been much research and scientific evidence regarding the activity of the faloak plant as a herbal ingredient. The purpose of this literature review is to determine the effect of the faloak plant as an antioxidant. For this reason, a literature search was carried out by searching for articles in research journal databases. From the results of this literature search, it was found that there was significant antioxidant activity in the use of extracts of the bark and roots of Sterculia quadrifida which showed the strongest antioxidant activity compared to leaves, fruits and seeds. The best antioxidant activity was found in 95% ethanol extract for plant bark and 70% ethanol for plant roots. It is because of the identification of the secondary metabolites contained in this plant, including alkaloids, phenols, flavonoids, terpenoids and tannins which are known to act as anti-oxidants